2020
DOI: 10.1111/jocn.15292
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain, cardiovascular health and related medication use in ageing African Americans with osteoarthritis

Abstract: Aim and objectives To describe the (a) prevalence and perceptions of cardiovascular disease and related health conditions in African Americans with osteoarthritis pain, (b) their knowledge of cardiovascular safety of commonly prescribed analgesics for osteoarthritis and (c) frequency of high‐risk analgesic use. Background African Americans have more disabling osteoarthritis pain and an excessive burden of cardiovascular disease than any other US racial group. However, minimal research has investigated the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
(93 reference statements)
0
9
0
Order By: Relevance
“…The prevalence of hypertension was 80.9%, consistent with the high burden of CVDs in the African American population in general. The average pain score of patients with hypertension was not significantly higher than those without hypertension or the overall sample, 13 and we identified the lack of reliable measurements of exposure and its limited statistical approach. The qualitative section of this study was exploratory, using semistructured interviews to determine the perception of CVDs and associated health conditions by African American participants with pain caused by osteoarthritis.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The prevalence of hypertension was 80.9%, consistent with the high burden of CVDs in the African American population in general. The average pain score of patients with hypertension was not significantly higher than those without hypertension or the overall sample, 13 and we identified the lack of reliable measurements of exposure and its limited statistical approach. The qualitative section of this study was exploratory, using semistructured interviews to determine the perception of CVDs and associated health conditions by African American participants with pain caused by osteoarthritis.…”
Section: Resultsmentioning
confidence: 80%
“…The fourth study was an MMS of the convergent parallel type, 13 which means that the quantitative and qualitative strands of the research are performed independently but simultaneously, and their results are brought together in the overall interpretation. 5,14 The objective of the quantitative section was to evaluate the prevalence and perceptions of cardiovascular diseases (CVDs) and related health conditions in a US African American population with osteoarthritis pain phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple pieces of evidence indicate that chronic pain is associated with abnormal psychological stresses (9)(10)(11), and patients with chronic pain presented ECG changes including AF (12). In fact, acute or chronic pain is associated with an increased risk of cardiovascular disease (13)(14)(15). A systematic review demonstrated that chronic pain was significantly associated with mortality caused by cardiovascular disorders and implicated a possible dose-response relationship (16).…”
Section: Introductionmentioning
confidence: 99%
“…The largescale genome-wide association study (GWAS) of CAD (coronary artery disease) and migraine pointed out the common susceptibility gene locus PHACTR1 (encoding phosphatase and actin regulator 1 protein) of the common mechanism of the two diseases (Winsvold et al, 2017a). Chronic pain and CVD often occur simultaneously, but the mechanisms of comorbidities remain unclear (Birnbaum et al, 1997;Winsvold et al, 2015b;Winsvold et al, 2017b;Tesarz et al, 2019;Booker and Content, 2020). The relationship between pain and CVD is not well defined.…”
Section: Introductionmentioning
confidence: 99%